The Happiness in a Digital World – The Associations of Health, Family Life, and Digitalization Perceived Challenges - Path Model for Abu Dhabi: none - Masood Badri; Mugheer Alkhaili; Hamad Aldhaheri; Guang Yang; Muna Albahar; Asma Alrashdi (Journal of Social Science, 2023)
The digital revolution influenced all levels and spheres of human social activities covering personal communications and relationships, health and mental health, and hours spent online. However, the widespread implementation and effects of digital technologies amongst all segments of society have not been understandable. The effects touch all aspects of life, be it personal, social, or economic, touching people's happiness positively or negatively. This research is the first attempt in Abu Dhabi to look at the impact of digital transformation and the associations of other aspects of people's life. The objective of this study is to propose a path model for better understanding the degree of association of related behaviors related to digital transformation and people's happiness. An extensive literature search identified several related wellbeing dimensions for this study. We used the Abu Dhabi Quality of Life data for this purpose. Pre-analysis included correlation analysis, simple and multiple regression, factor analysis, and reliability analysis to test the appropriate variables. The final path model portrays the functional relationship between significant factors, with happiness being the ultimate variable. The dimensions of influence covered satisfaction with family life, subjective health, mental and related feelings, number of hours online, the perception of the positive impact of digitalization on society, and the perceived negative influence of digitization. Using LISREL, we designed and analyzed a reflective path model that produced significant fit statistics. Results show that we should not ignore the significant positive association between the digital resources/means in society and our happiness or health. However, results also point to the perception of the negative impact of digital transformation on how we feel and behave daily. The hours we spend online also add to our negative daily feelings. The nature of our satisfaction with our family life seems to influence our negative mixed feelings about digital practices and habits. The strong association between our overall happiness and subjective health produced the most significant association. Limitations and policy implications are discussed.